Changes in Education: Towards a New Paradigm - Koutsopoulos, K. C (Advances in Social Sciences Research Journal, 2024)
This paper in reacting to the reality of the present days education system suggests that there is a need to work within a susceptible to present conditions educational paradigm. More specifically, the unambiguous position of this paper is that a new paradigm shift has appeared in teaching and learning leading to alterations of operating within, between and outside the classrooms as a result of the changes that have taken place of the principal dimensions of education such as: the form and approach to teaching and learning; the factors responding to the evolution and adaptation to changing needs and expectations in education; and the way education is perceived and practiced through time. This new paradigm, the integration-centred, should replace the student-centred, which itself has replaced the teacher-centred one. Therefore, the paper presents a new paradigm, which should be based on the integrated dimension of education, where the importance of the effectiveness and efficiency of teaching and learning implies a tautological integrated approach in considering education.